2013
DOI: 10.1111/tger.10131
|View full text |Cite
|
Sign up to set email alerts
|

From Broadway to Berlin: Transformative Learning through German Hip‐Hop

Abstract: This article explores the possibilities for effecting Transformative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…More recent work linking transformative learning to FL study has pointed to the language classroom as a rich site for students to question how and why cultures differ. Learning outcomes identified in research on transformative learning in FL learning contexts have included: deepening students’ understanding of culture, both of the target language and of their own (Goulah, 2007; Ivers, 2007; Johnson, 2015; King, 2000; Sosulski, 2013), shifts in how learners view and position themselves to the target language and its cultures (Crane, 2018; Johnson & Mullins Nelson, 2010; Johnson, 2015), and changes in how they see themselves as language learners (Johnson, 2015; King, 2000). In the following, we trace recent L2 learner studies that adopt an explicit transformative learning approach to describe what perspective transformation and their attendant pedagogies may look like in FL instruction.…”
Section: Transformative Learning and Structured Reflectionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent work linking transformative learning to FL study has pointed to the language classroom as a rich site for students to question how and why cultures differ. Learning outcomes identified in research on transformative learning in FL learning contexts have included: deepening students’ understanding of culture, both of the target language and of their own (Goulah, 2007; Ivers, 2007; Johnson, 2015; King, 2000; Sosulski, 2013), shifts in how learners view and position themselves to the target language and its cultures (Crane, 2018; Johnson & Mullins Nelson, 2010; Johnson, 2015), and changes in how they see themselves as language learners (Johnson, 2015; King, 2000). In the following, we trace recent L2 learner studies that adopt an explicit transformative learning approach to describe what perspective transformation and their attendant pedagogies may look like in FL instruction.…”
Section: Transformative Learning and Structured Reflectionmentioning
confidence: 99%
“…Within the context of beginning FL instruction, written reflections have been found to elicit from students rich connections between their language learning experiences in and beyond the classroom walls (Crane, 2018). Educators who have studied transformative learning in study abroad and advanced undergraduate coursework (Anderson & Cunningham, 2010; Cunningham, 2010; Grossman, 2009; Sosulski, 2013) have conceptualized SR as connecting three different domains for understanding: learners’ past and current experiences, their beliefs and assumptions, and theoretical and conceptual knowledge. This triangular model is depicted in Figure 1 below.…”
Section: Transformative Learning and Structured Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the problem of cultural essentialization and assumptions about cultural standards, it was necessary to increase students' awareness of their preconceptions about hip-hop. Students in the class demonstrated that preexisting associations with hip-hop in the U.S. were carried over into the German context in some examples, mirroring results from Putnam (2006) and Sosulski (2013). However, this music video varied from previous studies because OK KID's portrayal of the phenomena of racism and ethnocentric standards pairs a surface-level denial of racism with racist imagery.…”
Section: Overview Of the Lessonmentioning
confidence: 82%
“…
This observational study examines the use of the German hip-hop music video, "Gute Menschen" by the band OK KID (2015), as a basis for developing students' symbolic competence regarding contemporary discourse on racism in Germany. Based on earlier investigations (Putnam, 2006;Sosulski, 2013), this article advocates for the use of German music videos to develop students' abilities to decode multimodal symbols (i.e., visual, musical, and lyrical symbols) individually and holistically. Existing research supports the use of target language music videos in beginner-and intermediate-level lessons because of their affective and aesthetic properties (
…”
mentioning
confidence: 99%